A Multi-epitope Vaccine Candidate Against Bolivian Hemorrhagic fever Caused by Machupo Virus - Ali, Zeeshan; Cardoza, Jyothsna Volisha; Basak, Srijita; Narsaria, Utkarsh; Bhattacharjee, Surjit; G, Unnati Meher; Isaac, Samuel Paul; Franca, Tanos C C; LaPlante, Steven R; George, Sudhan S (Applied biochemistry and biotechnology, 2024)
Bolivian hemorrhagic fever (BHF) caused by Machupo virus (MACV) is a New World arenavirus having a reported mortality rate of 25-35%. The BHF starts with fever, followed by headache, and nausea which rapidly progresses to severe hemorrhagic phase within 7 days of disease onset. One of the key promoters for MACV viral entry into the cell followed by viral propagation is performed by the viral glycoprotein (GPC). GPC is post-transcriptionally cleaved into GP1, GP2 and a signal peptide. These proteins all take part in the viral infection in host body. Therefore, GPC protein is an ideal target for developing therapeutics against MACV infection. In this study, GPC protein was considered to design a multi-epitope, multivalent vaccine containing antigenic and immunogenic CTL and HTL epitopes. Different structural validations and physicochemical properties were analysed to validate the vaccine. Docking and molecular dynamics simulations were conducted to understand the interactions of the vaccine with various immune receptors. Finally, the vaccine was codon optimised in silico and along with which immune simulation studies was performed in order to evaluate the vaccine's effectiveness in triggering an efficacious immune response against MACV.
Keywords: Machupo virus; americká hemoragická horečka; simulace molekulového dockingu; arenaviry Nového světa; Molecular docking; Immune simulation; lidé; Arenaviruses, New World; Molecular Dynamics Simulation; Molecular dynamics simulation; Molecular Docking Simulation; Viral Vaccines; virové vakcíny; Humans; simulace molekulární dynamiky; Hemorrhagic Fever, American; Epitopes; Multi-epitope vaccine; epitopy